Controlling molecular packing via diffusion methods for enhanced photochromic properties in D-A hybrid heterostructures. (February 2021) - You, Ming-Hua; Li, Meng-Hua; Liu, Jing-Yan; Lin, Mei-Jin
Abstract: Donor-acceptor (D-A) hybrid heterostructures, an emerging class of crystalline hybrid complexes composed of semiconducting organic and inorganic components, have attracted much attention as photochromic materials. Among them, photochromic polyoxometalate/naphthalenediimide D-A hybrid heterostructures represent the most investigated ones, whose photochromic properties are strongly dependent on the structures of polyoxometalates and naphthalenediimides. Herein, we reported their photochromic properties are controlled by their moculelar packings, which were achieved by their diffusion methods. Eight polyoxometalate/naphthalenediimide D-A hybrid heterostructures have been synthesized by the combinations of metal salts (ZnSiF6 ·6H2 O or Zn(ClO4 )2 ·6H2 O), heteropoly acid (H3 PMo12 O40 or H3 PW12 O40 ) and N, N -di (4-pyridyl)-1, 4, 5, 8-naphthalene diimide (DPNDI) via two diffusion methods (A and B). Interestingly, single-crystal X-ray diffraction analyses reveal that they belong to three categories of isostructures with layered, sandwich and interpenetrating packing patterns. Their photochromic properties have been carefully investigated, and the impacts of polyoxometalates as well as packing patterns have also been discussed. Graphical abstract: Image 1 Highlights: Eight polyoxometalate/naphthalenediimide D-A hybrid heterostructures have been synthesized via two diffusion methods. Their structures belong to three categories of isostructures with layer, sandwich and interpenetrating packing patterns. The effects of POM anions in the their photochromic properties are mainly dependent on their initial absorptions. The impacts of molecular packing patterns are different with the irradiation time. This work opens a new door for the regulation of photochromic properties by molecular packing via diffusion methods.